The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1287/orsc.1110.0662
|View full text |Cite
|
Sign up to set email alerts
|

Building Employee Commitment to Change Across Organizational Levels: The Influence of Hierarchical Distance and Direct Managers' Transformational Leadership

Abstract: Research has shown that employees' affective and normative commitment to change (ACC and NCC, respectively) positively influence their behaviors supporting change; however, organizations are frequently unsuccessful in motivating appropriate levels of employee commitment to change. Using longitudinal, multilevel data collected from a large federal government agency implementing radical organizational change, we extend extant research related to antecedents of commitment to change by examining how employees' hie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
114
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(135 citation statements)
references
References 78 publications
8
114
0
2
Order By: Relevance
“…Brief, Aldag and Wallden, (1976), investigated police officers' commitment and found high positive relationship between respect for their supervisors and organizational structuring level. Den Hartog and Belschak (2012), Hill, Seo, Kang, and Taylor (2012) and Mowday, et al (1982) also found that there was a positive relationship between leader's behavior and employees' commitment. Lee (2008) found out that transformational leadership significantly correlates with employees' commitment with the sample of professionals in Singapore.…”
Section: The Relationship Between Transformational Leadership Styles mentioning
confidence: 97%
“…Brief, Aldag and Wallden, (1976), investigated police officers' commitment and found high positive relationship between respect for their supervisors and organizational structuring level. Den Hartog and Belschak (2012), Hill, Seo, Kang, and Taylor (2012) and Mowday, et al (1982) also found that there was a positive relationship between leader's behavior and employees' commitment. Lee (2008) found out that transformational leadership significantly correlates with employees' commitment with the sample of professionals in Singapore.…”
Section: The Relationship Between Transformational Leadership Styles mentioning
confidence: 97%
“…This reinforces the importance of Bottomup communication of team members in the Vanguard Method, which is of paramount importance in enhancing employees self-esteem and personal importance and this, in return, helps to build employees affective commitment (Hill et al 2012). It is, therefore, evident that team members have the ownership of their work (Meyer and Allen 1991).…”
Section: Given This New Hierarchical Context the Vanguard Methods Promentioning
confidence: 53%
“…As a result, hierarchical distance from top management is reduced. Hill et al (2012) argued that the smaller the hierarchical distance from top management the smaller is the discrepancy between team members and top management's uniformity of purpose and vision, thus, the higher the level of trust and faith in top management. This has been associated with higher levels of employees affective commitment toward the organization (Wanous et al 2000).…”
Section: Affective Commitment: Impact On Organisational Resiliencementioning
confidence: 99%
“…It is important to note that even those involved in the decision-making process, regardless of their position within the organization, may not be supportive of the final choice to enact the harm-doing event. Dissent against strategic decisions can occur at all levels of an organization (Hill et al 2012), regardless of collective outcomes.…”
Section: Managerial Harm-doing Responsibility Attribution Modelmentioning
confidence: 99%